The trap-jaw ant genus Odontomachus Latreille (Hymenoptera: Formicidae) from Sumatra, with a new species description - Satria, Rijal; Kurushima, Hiroaki; Herwina, Henny; Yamane, Seiki; Eguchi, Katsuyuki (Zootaxa, 2015)
The ant genus Odontomachus Latreille is reviewed for Sumatra, the sixth largest island in the world and located in western Indonesia. Previously three species were recorded from the island: O. simillimus F. Smith, O. rixosus F. Smith, and O. latidens Mayr. We add two species to the fauna, O. procerus Emery stat. nov and Odontomachus minangkabau sp. nov. The new species belongs to O. rixosus species group, and it is morphologically most similar to O. rixosus and O. pararixosus Terayama & Ito. However, it can be separated from the latter two by its large body (HL 3.13–3.55 mm, WL 4.15–4.65 mm), the masticatory margin with 11–14 denticles, and dark-colored body. Odontomachus latidens subsp. sumatranus Emery is newly synonymized with O. procerus. The castes and sexes of the known species are also described, including the first descriptions of the male for O. latidens, O. procerus, and O. rixosus. A key to the Sumatran species based on the worker caste is provided, and the bionomics of each species is summarized.